2006
DOI: 10.2320/matertrans.47.156
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Cobalt, Nickel, and Titanium by Cold-Crucible Induction Melting in Ultrahigh Vacuum

Abstract: Three separate charges of cobalt 9.2 kg in weight, 3.0 kg nickel and 1.6 kg titanium have been melted in ultrahigh vacuum (UHV) using cold-crucible induction melting (CCIM) furnace, in which UHV of better than 1 Â 10 À7 Pa is attainable. The effects of CCIM in UHV on the purification of these metals due to the removal of gaseous impurities, and the characteristics of CCIM in UHV have been investigated by the analysis of the melting conditions such as the total pressure and the mass spectra of gases during CCIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Takaki and Abiko [11] has reported that cold-crucible induction melting in an ultrahigh vacuum was effective to remove gaseous elements from Co. But another refining technique, H 2 -Ar plasma arc melting (which can deoxidize Co more rapidly) has been developed by Mimura et al [12] Thus, H 2 -Ar plasma arc melting was employed to remove oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Takaki and Abiko [11] has reported that cold-crucible induction melting in an ultrahigh vacuum was effective to remove gaseous elements from Co. But another refining technique, H 2 -Ar plasma arc melting (which can deoxidize Co more rapidly) has been developed by Mimura et al [12] Thus, H 2 -Ar plasma arc melting was employed to remove oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…10 Treatment and purification of Ti─Al alloys, 11 iron, 12 cobalt, nickel, and titanium 13 as well as extraction of noble gases 14 and preparation of expansible graphite 15 have been well reported in the literatures. 10 Treatment and purification of Ti─Al alloys, 11 iron, 12 cobalt, nickel, and titanium 13 as well as extraction of noble gases 14 and preparation of expansible graphite 15 have been well reported in the literatures.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the induction heating of synthesized MgFe 2 O 4 particles has been reported at inert atmosphere and frequency of 265 kHz, whereas the aim was not desulfurization. 10 Treatment and purification of Ti─Al alloys, 11 iron, 12 cobalt, nickel, and titanium 13 as well as extraction of noble gases 14 and preparation of expansible graphite 15 have been well reported in the literatures. Likewise, the desulfurization of carbon saturated iron has been investigated in induction furnace by sodium carbonate and sodium sulfate 16 ; however, the induction heating of coke breeze has not been reported because of its diamagnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Induction melting with cold copper crucible in vacuum can avoid contamination from refractory of crucibles and is also effective to remove the gaseous impurities in metal and alloys. A newly developed method for melting and controlled solidification of metals in the same vessel was outlined in our previous works [1]. However, the cost of IFCC (the induction furnace with cold crucible) is still very high due to its large heat loss and power consumption.…”
Section: Introductionmentioning
confidence: 99%